EFFECTIVENESS OF CRYOTHERAPY VERSUS THERMAL THERAPY IN REDUCING PAIN IN ACUTE ANKLE SPRAIN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Iffat, Fatima Azhara; Pitaloka, Ganis Sekar Dhea; Indraprastha, Annya Shakty; Putri, Risma Salsabila Isnaini; Altrisnisa, Anindya Syaharani; Pristianto, Arif (CV. Fahr Publishing, 2025)
This study aims to compare the effectiveness of cryotherapy and thermal therapy in reducing pain among patients with acute ankle sprain. A systematic search was conducted using PubMed, Google Scholar, and Scimago databases, yielding 907 articles. After applying strict inclusion criteria, seven randomized controlled trials (RCTs) with a total of 203 participants were included in the meta-analysis. Data were analyzed using Review Manager 5.3 with a random-effects model, and methodological quality was assessed using the PEDro Scale. The meta-analysis showed no statistically significant difference between cryotherapy and thermal therapy in pain reduction, with a Standardized Mean Difference (SMD) of 0.09 (95% CI: -0.90 to 1.08) and substantial heterogeneity (I² = 88%). Funnel plot analysis indicated potential publication bias. Despite the high methodological quality of the included studies, variations in intervention type, duration, and patient population limit the generalizability of the findings. This study offers a novel contribution by being one of the few meta-analyses to directly compare these two modalities specifically in acute cases. The findings support flexible, evidence-based clinical decision-making tailored to individual patient needs and available resources.